Magnetic transition and large magnetocaloric effect associated with surface spin disorder in Co and CocoreAgshell nanoparticles - Poddar, P.; Srinath, S.; Gass, James; Bhagavatula L. V. Prasad; Srikanth, H. (Journal of Physical Chemistry C, 2007)
We report a reversible, large magnetocaloric effect in the vicinity of a low-temperature magnetic transition in Co and CocoreAgshell nanoparticles synthesized using a wet chemical method. The as-synthesized assembly of the particles shows a sharp low-temperature peak in the zero-field-cooled (ZFC) magnetization well below the blocking transition temperature, and this feature is associated with the surface spin disorder. Co nanoparticles show a large increase in the magnetic entropy at around 15 K with a peak value of nearly 2.25 J/K center dot kg for an applied field of 30 kOe. A similar trend is also observed in the silver-coated Co particles. These are some of the largest NICE values observed in nanoparticles to date. The features are ascribed to the low-temperature spin-glass-like freezing transition associated with the surface spins in the shell region that is distinct from the behavior of core spins. Our studies reveal that manipulating the surface anisotropy in core-shell nanoparticles has the potential to lead to a large NICE effect and thus prove to be useful for magnetic refrigeration.